Diagnóstico comunitario de salud del Barrio San Agustín sector I, septiembre-diciembre de 2013 - Benitez Caraguay, Silvia Patricia (2013)
The present study “DIAGNÓSTICO COMUNITARIO DE SALUD DEL BARRIO SAN AGUSTIN SECTOR I, SEPTIEMBRE-DICIEMBRE 2013," is framed in the macro project LA CARRERA DE ENFERMERIA EN LA ATENCION INTEGRAL DEL SISTEMA NACIONAL DE SALUD FAMILIAR COMUNITARIO E INTERCULTURAL, HOSPITAL UNIVERSITARIO DE MOTUPE, SEPTIEMBRE-DICIEMBRE DE 2013, aims to contribute to the social development of the town , bringing with statistical data that will enable them to basic health teams Motupe University Hospital , develop strategies for maintaining and improving the health of individuals, families and communities, from a biopsychosocial , multidisciplinary and intercultural approach. The study was Descriptive type , emphasizes the analysis and interpretation of the facts and the methodology relied on strategies established in the comprehensive care model of health, such as Home Visit Family Listing to apply and interview guide that allowed complete information to the baseline , where priority problems were identified to take appropriate technical and political decisions to the local reality seeking to optimize institutional responses and encourage community participation in improving health conditions . ( Guerrero and Slimming , 2009:4 ) . Among the most relevant indicators such as prevalence data excel, male , level of basic education, / as heads of households are engaged in activities such as household chores , farming , masonry . Schoolchildren and adolescents in cases of malnutrition and overweight and most of them studying appreciated. Family planning for women of childbearing age, the rhythm method is the most widely used. The epidemiological profile of chronic diseases prevalent hypertension. Keywords : Community Health Diagnostic , Epidemiological Profile